2022
DOI: 10.1212/wnl.0000000000200113
|View full text |Cite
|
Sign up to set email alerts
|

Association of Motor and Nonmotor Symptoms With Health-Related Quality of Life in a Large Online Cohort of People With Parkinson Disease

Abstract: Background:There is growing interest in health-related quality of life (HRQOL) as a comprehensive view of the patient’s well-being, guiding concept for the treating clinician, and therapeutic trial outcome measure for patients with PD. The key determinants of HRQOL have not been investigated in large populations of people with PD (PwPD). Our objective was to evaluate correlates of health-related quality of life (HRQOL) in a large, online cohort of PwPD.Methods:As part of an ongoing online cohort study, we perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 53 publications
(69 reference statements)
1
20
0
Order By: Relevance
“…Studies have shown that women having more fatigue levels are prone to poorer quality of life and depression (18), this supports our study where women scored more on the salivary cortisol levels. Salivary cortisol has been correlated with stress, risky behavior responses, depression few studies have shown a strong positive correlation (19).…”
Section: Discussionsupporting
confidence: 91%
“…Studies have shown that women having more fatigue levels are prone to poorer quality of life and depression (18), this supports our study where women scored more on the salivary cortisol levels. Salivary cortisol has been correlated with stress, risky behavior responses, depression few studies have shown a strong positive correlation (19).…”
Section: Discussionsupporting
confidence: 91%
“…PD is clinically manifested by cardinal symptoms of bradykinesia (slowness of movement), rigidity, or stiffness that impedes normal motor activities, and/or rest tremor 180 . The motor symptoms of PD are frequently disabled and significantly affect daily function 181 . Although the primary pathologic mechanisms driving the neurodegenerative processes in PD have not yet been fully identified, the hypokinetic symptoms, bradykinesia, and rigidity have been linked to the loss of dopamine (DA) neurons within the substantia nigra pars compacta (SNc) and the resulting reduction of striatal DA tone 182–184 .…”
Section: Ttccs In Parkinson's Diseasementioning
confidence: 99%
“… 180 The motor symptoms of PD are frequently disabled and significantly affect daily function. 181 Although the primary pathologic mechanisms driving the neurodegenerative processes in PD have not yet been fully identified, the hypokinetic symptoms, bradykinesia, and rigidity have been linked to the loss of dopamine (DA) neurons within the substantia nigra pars compacta (SNc) and the resulting reduction of striatal DA tone. 182 , 183 , 184 Importantly, DA is a major regulator of the BG motor circuit (Figure 5 ), and degeneration of the SNc is correlated with changes in neuronal activity in BG circuits.…”
Section: Ttccs In Parkinson's Diseasementioning
confidence: 99%
“…Tese NMS include but are not limited to cognitive decline, mood and sleep disturbances, an impaired sense of smell, and a wide range of gastrointestinal symptoms [3,4]. In fact, research indicates that the NMS of PD may have a greater impact on health-related quality of life than the cardinal motor symptoms [5,6]. As PD does not have a cure or treatment to slow disease progression, research needs to focus on identifying factors that can be treated to improve patient quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…In complex, progressive disorders, like Parkinson's disease, with a wide range of motor and nonmotor symptoms, QoL is an important factor to consider when managing the disease as each individual will be unique, in terms of the combination of symptoms at any particular time-point in the course of the disease. Although constipation can afect QoL in PwP [6,8,9], gastrointestinal symptoms remain as the top underreported [10,11], and thus, untreated symptoms in PD [5], leading to suboptimal clinical care and poorer QoL [12]. Whereas the adverse efects of other NMS such as cognitive impairment [13,14] and sleep disturbances [15,16], on QoL in PD are well-documented, the impact of gastrointestinal symptoms on QoL in PD populations has received relatively little attention in the literature.…”
Section: Introductionmentioning
confidence: 99%